Phase II study of dasatinib in patients with previously treated malignant mesothelioma (Cancer and Leukemia Group B 30601): a brief report - Dudek, Arkadiusz Z. (2012)
INTRODUCTION: We conducted a phase II trial of dasatinib in malignant mesothelioma (MM) patients to evaluate its toxicity and efficacy as a second-line treatment. MATERIAL AND METHODS: Patients with unresectable MM and no symptomatic effusions were given dasatinib 70 mg twice daily as part of a 28-day cycle. We also measured plasma VEGF and PDGFβ and serum CSF-1 and mesothelin-related protein at baseline and during therapy. RESULTS: Forty-six patients were enrolled in this study. Fifty percent of the first 12 patients enrolled experienced ≥ grade 3 treatment-related adverse events, and therefore, the starting dose was reduced to 50 mg twice daily. Grade 3 and 4 toxicities included fatigue (11%) and pleural effusion (9%). The overall disease control rate was 32.6%, and PFS at 24 weeks was 23% (95% CI: 13.5%, 40.0%). Survival was markedly longer in patients with lower pre-treatment CSF-1 levels and in patients whose CSF-1 levels decreased from baseline during therapy. DISCUSSION: Single-agent dasatinib has no activity in MM and is associated with pulmonary toxicities that prohibit its use in an unselected MM population.